2017
DOI: 10.1007/s11999-017-5476-5
|View full text |Cite
|
Sign up to set email alerts
|

PROMIS Pain Interference and Physical Function Scores Correlate With the Foot and Ankle Ability Measure (FAAM) in Patients With Hallux Valgus

Abstract: The relationships shown here between PROMIS and FAAM scores further support the use of PROMIS tools in outcomes-based research. In patients with hallux valgus, pain-related disability appears to be a central feature of the patient-experience. Future studies should assess the association of various outcome domains on other common foot and ankle diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…PROMIS has been shown to be a reliable and efficient method of collecting PROs, making it an attractive alternative to legacy measures. 3,10,14,17 In addition, PROMIS scores have been validated for foot and ankle outcome measures. 2,11 Consistent with several studies, 2,[4][5][6][7]9,19 this study supports that preoperative PROs can be a useful tool for discussing postoperative treatment goals and expectations for domains such as PF.…”
Section: Discussionmentioning
confidence: 99%
“…PROMIS has been shown to be a reliable and efficient method of collecting PROs, making it an attractive alternative to legacy measures. 3,10,14,17 In addition, PROMIS scores have been validated for foot and ankle outcome measures. 2,11 Consistent with several studies, 2,[4][5][6][7]9,19 this study supports that preoperative PROs can be a useful tool for discussing postoperative treatment goals and expectations for domains such as PF.…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 40 , 41 Additionally, multiple studies in the literature have emerged to support the use of the PIF CAT as an important augmentation to capturing physical function in patients with pain. 27 , 34 , 42 Kendall et al. 43 correlated the PIF CAT with the PF CAT in a population of patients presenting with spinal pain and concluded that the PIF CAT is a useful augmentation to physical function measures.…”
Section: Discussionmentioning
confidence: 99%
“…PROMIS data—specifically, physical function, pain interference, and depression scores—were captured at every clinic appointment electronically using previously defined and validated criteria. 10 To briefly review, a PROMIS score of 50 represents a population average, and 10-point changes represent a standard deviation from that average. Higher scores in negatively worded questions like PROMIS pain interference and depression represent more disability (ie, greater pain and more depression), whereas larger PROMIS physical function scores indicate greater function.…”
Section: Methodsmentioning
confidence: 99%